Application of Cryopreserved Packed Red Blood Cells to Treat Anaemic Syndrome in Canine Babesiosis - Pervushina, O. A. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):186.